Study and application of Symphonie model to compute the hydrodynamic processes in the East Sea - Thai, To Duy; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2019)
Hydrodynamic processes in the East Sea have been studied by many Vietnamese and foreign scientists applying the models as advanced tools with low cost and spatial and temporal synchronized dataset to serve their research. However, applying the model to study variability of small and medium structures with very high resolution (a few kilometers) is still challenge for scientists. With the advantages of high quality real-time data, open source hydrodynamic model, and the support from high performance computer (HPC) systems, we have step by step studied and developed the numerical model for study on hydrodynamic fields in the East Sea. The model was validated with high resolution satellite data as well as in-situ data from the ARGO and research vessels. Initial results of the simulation are very good for the surface seawater temperature (SST) field in the East Sea.